INVESTIGATING THE ATTITUDES TOWARDS LEARNING CALCULUS AMONG SCIENCE AND TECHNOLOGY STUDENTS: A CASE STUDY IN UITM JOHOR, MALAYSIA - Nor Hidayah Hassim,; Siti Hasma Hajar Mat Zin,; Muhammad Yassar Yusri, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Calculus is widely regarded as one of the difficult branches of Mathematics and is considered an intimidating subject even to Science and Technology students. Majority of the students find themselves struggling. This is due to the fact that a student's attitude has an impact on how effectively they learn Calculus and as a result, affecting their performance in course grades in university level. Therefore, this study was conducted to investigate the students’ attitude towards Calculus at UiTM Segamat Branch, Johor. This study also aims to determine the differences in attitudes scores between program courses and gender as well as to examine the relationship between students’ attitude and their Calculus achievement. The target population of this study is undergraduate students comprising Diploma in Computer Science (CS110) and Diploma in Mathematical Sciences (CS143) students who have enrolled in Calculus subject. Data was collected using an online questionnaire and a cross-sectional research design was used for this study. Descriptive statistics such as mean and standard deviation, independent t-test and correlation analysis were conducted. The findings of this study revealed that students showed a positive moderate attitude towards Calculus. Meanwhile, there is no significant difference in attitudes scores across program courses as well as gender. Also, students with a negative attitude tend to have a low level in terms of Calculus achievement. Students’ attitudes towards Calculus may change over time because it could be influenced by other elements but the most important element that influences the students are lecturers. In order to encourage the development of a positive attitude towards Calculus, lecturers must constantly monitor students' attitudes toward the subject and offer the necessary support.